2005
DOI: 10.5326/0410388
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Selamectin in the Treatment of Naturally Acquired Infection of Sucking Lice (Linognathus setosus) in Dogs

Abstract: A clinical study was performed in 21 dogs to evaluate the efficacy of selamectin for the treatment of naturally acquired infection of sucking lice (Linognathus setosus [L.setosus]) in dogs. Each dog was randomly assigned to one of two treatment groups. One group was treated with selamectin applied topically at a mean dosage of 7.9 mg/kg. The other group was treated with permethrin applied topically at a mean dosage of 85.7 mg/kg. At day 42 posttreatment, all animals remaining in the study (10 treated with sela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 3 publications
3
11
0
1
Order By: Relevance
“…SEL is widely used to control ectoparasites, such as ticks, lice, fleas, and mites, (Dryden et al 2007;Franc and Yao 2007;Gunnarsson et al 2005;Jernigan et al 2000;Kim et al 2008;Kurtdede et al 2007;Miller et al 2006;Shanks et al 2003), as well as some nematodes (Hill et al 2006;Gönenç et al 2006;Ozkanlar et al 2004;Silverman 2006;Tudor et al 2008). In clinical trials, it was found to be a highly effective and broad-spectrum drug that was safe for animals (including rhesus macaques, dogs, cats, rats, rabbits, and ferrets; Esatgil et al 2008;Fisher and Shanks 2008;Kim et al 2008;Miller et al 2006;Wang et al 2008a).…”
Section: Discussionmentioning
confidence: 97%
“…SEL is widely used to control ectoparasites, such as ticks, lice, fleas, and mites, (Dryden et al 2007;Franc and Yao 2007;Gunnarsson et al 2005;Jernigan et al 2000;Kim et al 2008;Kurtdede et al 2007;Miller et al 2006;Shanks et al 2003), as well as some nematodes (Hill et al 2006;Gönenç et al 2006;Ozkanlar et al 2004;Silverman 2006;Tudor et al 2008). In clinical trials, it was found to be a highly effective and broad-spectrum drug that was safe for animals (including rhesus macaques, dogs, cats, rats, rabbits, and ferrets; Esatgil et al 2008;Fisher and Shanks 2008;Kim et al 2008;Miller et al 2006;Wang et al 2008a).…”
Section: Discussionmentioning
confidence: 97%
“…They spend their entire life on one host, and several lice species prefer specific locations on the host’s body. Predilection sites for lice are the head including ears, neck and back of the dog [ 4 , 5 ]. Lice are usually unable to survive off the host animal for more than 2 days [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Predilection sites for lice are the head including ears, neck and back of the dog [ 4 , 5 ]. Lice are usually unable to survive off the host animal for more than 2 days [ 3 , 4 ]. Thus, lice are mainly spread by direct physical contact between individuals; contaminated brushes or combs can also transmit these parasites [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations